2020
DOI: 10.1177/0891242420907160
|View full text |Cite
|
Sign up to set email alerts
|

Incentivizing the Missing Middle: The Role of Economic Development Policy

Abstract: The shrinking middle class and increasing income polarization in the United States are issues of concern to policy makers and others. Economic development incentives are a key policy tool used at the state and local levels to promote local economic growth, and, presumably, provide employment opportunities. However, these incentives may have unintended consequences that may be contributing to the decline of the middle class. The authors combine detailed industry-level detail on incentives with proprietary count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Previous studies have suggested an interactive mechanism between economic development and population inflows. High-quality and sustainable economic growth accelerates the accumulation of human capital, as well as the population flows between regions, thereby expanding the market scale of human capital [77]. Additionally, population inflows lead to the continuous expansion of the human capital scale, steady improvement in its quality, and optimization of its structure, injecting a constant source of momentum into sustainable economic growth.…”
Section: Endogeneity and Robustness Testsmentioning
confidence: 99%
“…Previous studies have suggested an interactive mechanism between economic development and population inflows. High-quality and sustainable economic growth accelerates the accumulation of human capital, as well as the population flows between regions, thereby expanding the market scale of human capital [77]. Additionally, population inflows lead to the continuous expansion of the human capital scale, steady improvement in its quality, and optimization of its structure, injecting a constant source of momentum into sustainable economic growth.…”
Section: Endogeneity and Robustness Testsmentioning
confidence: 99%
“…Human capital and sustainable economic growth promote each other and form a virtuous circle. First, in terms of quantity, high-quality and sustainable economic growth creates additional jobs, adequate innovation support, and favorable development opportunities for high-quality talents with new knowledge and skills; as a result, the market supply of human capital is maximized, and the flow and prosperity of human capital markets are promoted [24]. The increase of human capital stock improves the marginal productivity of individuals and slows down the decline of the marginal productivity of material capital [25].…”
Section: Interaction Between Human Capital and Sustainable Economic G...mentioning
confidence: 99%
“…I have spent a good portion of my career studying state and local economic development policies (Patrick, 2014a(Patrick, ,b, 2016b(Patrick, ,a, 2021bPatrick et al, 2017;Partridge et al, 2020;Patrick and Stephens, 2020). Within the literature, decision-makers can find support and evidence against the policy of interest (for recent overviews, see Neumark and Simpson, 2015;Bartik, 2018;Neumark and Young, 2019;Bartik, 2020;Slattery and Zidar, 2020;Hanson, 2021;Hanson and Rohlin, 2021).…”
Section: Introductionmentioning
confidence: 99%